First isolation of Flavobacterium psychrophilum associated with reports of moribund wild European eel (Anguilla anguilla) in Scotland. Issue 11 (27th August 2019) - Soares, Sílvia M. C.; Walker, Amanda; Elwenn, Svenja A.; Bayliss, Sion; Garden, Alison; Stagg, Hannah E. B.; Munro, Eann S.
Abstract: In late April 2015, the River Dee Trust informed Marine Scotland Science, Fish Health Inspectorate (FHI), that there had been observations of dead and moribund European eels on the River Dee. Later in May, the Spey Fishery Board also reported a number of moribund European eels in a rotary screw smolt trap on the River Spey. In total, 10 cases involving moribund eels were investigated in 2015 and one case in 2016. In addition, a health screen was conducted to investigate the potential presence of Flavobacterium psychrophilum in healthy eels and Atlantic salmon from the River Dee in 2015. Externally, the diseased eels demonstrated white patches in different locations of the body. In all cases, F. psychrophilum was detected by bacterial isolation and/or molecular methods. Three isolates were further characterized by whole‐genome sequencing (WGS) as belonging to sequence type 15 (ST15). Histological examination of diseased European eels revealed lesions at the level of the integument. The pathogen screen for F. psychrophilum in wild healthy fish tested negative by PCR. Further investigation is required to understand the pathogenicity of this bacterium on the health of eels and the potential impact on the wild salmonid population.